2016
DOI: 10.14411/fp.2016.011
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific morphometric variation in myxosporeans

Abstract: Abstract:Morphometric data from spores of ten myxosporean species were statistically analysed to explore myxosporean intraspecific variation in measurements when obtained from a sample from: (1) the same plasmodium, (2) different plasmodia from the same host and (3) different host individuals and localities. In some cases, significant differences in spore dimensions were found between samples from the same plasmodium, highlighting the difficulty of obtaining representative measurements of myxosporean spore. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 13 publications
3
5
0
Order By: Relevance
“…fuhrmanni found together in a cyst caused well observable tumors in the nostrils of the nase. Similar nodules with pathogenic characters were found in the skin of Cyprinus carpio infected by T. kitauei ( Egusa and Nakajima, 1981 ; Zhai et al, 2016 ; Liu et al, 2019 ) and in Cyprinella venusta infected by T. magnacysta ( Ksepka et al, 2020 ).…”
Section: Discussionsupporting
confidence: 71%
“…fuhrmanni found together in a cyst caused well observable tumors in the nostrils of the nase. Similar nodules with pathogenic characters were found in the skin of Cyprinus carpio infected by T. kitauei ( Egusa and Nakajima, 1981 ; Zhai et al, 2016 ; Liu et al, 2019 ) and in Cyprinella venusta infected by T. magnacysta ( Ksepka et al, 2020 ).…”
Section: Discussionsupporting
confidence: 71%
“…Morphological plasticity in myxospores are acknowledged to be one of the main factors responsible for the difficulties encountered in myxosporean taxonomy and species identification, resulting in taxonomic dilemmas (Zhai et al 2016, Guo et al 2018, Xi et al 2019. It is widely recognised that Ceratomyxa spp.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular analysis revealed that the two myxozoan samples share almost identical SSU rDNA sequences (99.6–99.8%). Considering the fact that intraspecific morphometric variation [ 11 ] and morphotypes [ 10 , 32 ] are common in myxozoans, the two samples from the gills of common carp were considered to be conspecific with each representing a morphotype of the same species, i.e. wide type (spores collected in 2013) and narrow type (spores collected in 2015).…”
Section: Discussionmentioning
confidence: 99%
“…However, there are exceptional cases that involve extensive intraspecific polymorphism, interspecific morphological similarity, identical interspecific biological traits, and blurred SSU rDNA-based species boundaries [ 8 11 ]. In these situations, if more than two of above exceptional cases are encountered at the same time, a systematist might again run into what we call a “taxonomic dilemma”.…”
Section: Introductionmentioning
confidence: 99%